2022
DOI: 10.1186/s12934-022-01816-2
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of BsGDH-CatIB variants and application as robust and highly active redox cofactor regeneration module for biocatalysis

Abstract: Background Catalytically active inclusion bodies (CatIBs) are known for their easy and cost efficient production, recyclability as well as high stability and provide an alternative purely biological technology for enzyme immobilization. Due to their ability to self-aggregate in a carrier-free, biodegradable form, no further laborious immobilization steps or additional reagents are needed. These advantages put CatIBs in a beneficial position in comparison to traditional immobilization techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 26 publications
(31 reference statements)
2
10
0
Order By: Relevance
“…Moreover, the enzyme assay revealed that no activity was measured for the insoluble cell pellet fraction. These results indicate that BsGDH WT did not form natural CatIBs, which con rms previous results from a manual BsGDH study (11).…”
Section: Insights On Structure/function Relationshipsupporting
confidence: 90%
See 4 more Smart Citations
“…Moreover, the enzyme assay revealed that no activity was measured for the insoluble cell pellet fraction. These results indicate that BsGDH WT did not form natural CatIBs, which con rms previous results from a manual BsGDH study (11).…”
Section: Insights On Structure/function Relationshipsupporting
confidence: 90%
“…3a, see Automated protein production and protein puri cation). For further investigation of this effect, we cultivated 48 biological replicates of E. coli BL21(DE3) with BsGDH-PT-CBDCell, a variant that was previously identi ed as a positive CatIB producer under standard conditions in a manual study (11). Strikingly, the nal backscatter values across the FlowerPlate varied from approx.…”
Section: Optimization Of the Catib Work Ow -Biolector Positional Biasmentioning
confidence: 99%
See 3 more Smart Citations